1010 Simba Study: Undergraduate Module in Simulation Training and Basic Life Support. (October 2012) - McElligott, F; Bruell, H; Viash, S; Nicholson, A; Molloy, E
Abstract : Background: Medical education has been greatly enhanced by the development of simulation 'patients.' Real-time training with simulated clinical signs promotes development and institution of practical management plans, without the fear of causing harm. We aimed to evaluate confidence levels and personal preference, as well as overall satisfaction with the module. Method: Students received pre-course reading material and three teaching sessions, including didactic teaching, video and live demonstrations, basic life support training using mannequins and small group teaching. The final session was a thirty-minute session in groups of 6, in which the students worked in teams to assess, diagnose and treat a simulation baby, followed by a case discussion. Students completed anonymous questionnaires. Results: 164 students completed the first two questionnaires, and 140 students completed the third. There were 44 postgraduate entry students: 10 Masters & 2 PhD graduates. 131 students felt they had benefited from the pre-course reading material and 130 students felt the 2-session pre-simulation were beneficial. Rated on a scale of 1–10, students' confidence increased by 2.6 points after the simulation session. Following the simulation, 73 students planned to increase their clinical versus their book work. 76 students requested 2 or more further hours of simulation teaching and 121 found the simulation baby to be superior to mannequins as a teaching tool. Discussion: The introduction of the SIMBA module was well received amongst medical undergraduates. Students gave positive feed back. Technological advances of simulation patients greatly add to paediatric undergraduate training, and enhance overall experience.